ANALYSIS OF THE EFFECTIVENESS OF GOVERNMENT PROGRAMS IN IMPROVING EDUCATION PARTICIPATION IN NIAS DISTRICT - Waruwu, Meiman Hidayat (Strategic Management Business Journal, 2025)
Research background: This study aims to analyze the effectiveness of government programs, especially the Smart Indonesia Program (PIP) and School Operational Assistance (BOS), in increasing education participation in Nias Regency. Purpose of the article: This study indicate that education participation in Nias Regency still faces significant challenges, especially those related to family economic factors, limited education infrastructure, and geographical distance between villages. The PIP and BOS programs have made a positive contribution to easing the burden of education costs, but have not been able to fully overcome the structural and cultural barriers that influence children's decisions to continue school. Methods: Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation from various related parties such as teachers, students, parents, and education officials.